Boosting Siamese Citrus Agribusiness through Upcycling and Tech Modernization - Shannon Leigh D Gabad; Neslie Martinez; Katherine Romero Mesa; Aleja C. Pasilaban; Jeffrey P. Penano; Michel P. Basister; Ni Luh Putu Indiani; Ida Bagus Udayana Putra; I Wayan Juliantara; Ni Rai Ayu Wisna (Community Service Journal (CSJ), 2024)
This study aims to assess the potential of upcycling waste products and integrating modern technologies to enhance the productivity and sustainability of the Siamese citrus agribusiness in Pelaga, Badung Indonesia. Sustainable practices and technological advancement in agriculture most likely to address environmental and economic challenges especially on the side of the small businesses. The research employs both qualitative and quantitative analyses. Face-to-face interview was conducted to a chosen citrus farm in Pelaga which needed aid in coming up with extra income aside from the “pre-ordered” oranges that are bought at a fixed price. A structured questionnaire and in-depth interview carried out with the farmer was used as a research instrument to gather data for assessing the viability of boosting the citrus agribusiness through upcycling, challenges they face and possible solutions and recommendations. The result of this study can be a benchmark for other farmers by demonstrating the tangible benefits of empowering farmers with knowledge and other tools to maximize their profit while adhering to zero-waste management, fostering a culture of continuous improvement in the agribusiness community.